Vertical habitat preferences shape the fish gut microbiota in a shallow lake - Zhang, Bowei; Xiao, Jiaman; Liu, Hongyan; Zhai, Dongdong; Wang, Ying; Liu, Shujun; Xiong, Fei; Xia, Ming (Frontiers in Microbiology, 2024)
Understanding the interactions between fish gut microbiota and the aquatic environment is a key issue for understanding aquatic microorganisms. Environmental microorganisms enter fish intestines through feeding, and the amount of invasion varies due to different feeding habits. Traditional fish feeding habitat preferences are determined by fish morphology or behavior. However, little is known about how the feeding behavior of fish relative to the vertical structure in a shallow lake influences gut microbiota. In our study, we investigated the microbial diversity of fish guts and their habitats in Lake Sanjiao and verified that the sediments indeed played an important role in the assembly of fish gut microbiota. Then, we traced the source of fish gut microbes using FEAST and found that microbiota in water and sediments acted as the primary sources in half of the fish gut microbiota respectively. Furthermore, we classified the vertical habitat preferences using microbial data and significant differences in both composition and function of fish gut microbiota were observed between groups with distinct habitat preferences. Moreover, the performance of supervised and unsupervised machine learning in classifying fish gut microbiota by habitat preferences actually exceeded classification by fish species taxonomy and fish trophic level. Finally, we described the stability of fish co-occurrence networks with different habitat preferences. Interestingly, the co-occurrence network seemed more stable in pelagic fish than in benthic fish. In this study, we advocated the use of microbial interactions between fish gut and their surrounding environment to reflect fish preferences in vertical habitat structure.